Improving Student Learning Outcomes Applying The Teams Games Tournament (TGT) Cooperative Learning Model in Class VIII Science Learning - Saputri, Ersa; Sriwahyuni, Eka; Fajriyani (Al-Khazini: Jurnal Pendidikan Fisika, 2023)
This research aims to improve science learning outcomes for class VIII A of SMP Muhammadiyah Parepare. This research is classroom action research (PTK). Observation, documentation and test results are the data collection techniques used, the data analysis technique used is the qualitative method, with research subjects in class VIII A of SMP Muhammadiyah Parepare. The results of this research prove that implementing the Teams Games Tournament (TGT) type cooperative learning strategy in receiving science material can improve student learning outcomes. This can be proven by the results of research on the application of the TGT learning model in initial conditions to improve the learning outcomes of class VIII A students at SMP Muhammadiyah Parepare with student learning outcomes only up to 25%, then reaching 55% in cycle one and 85% in cycle two, so that it can It is said that learning outcomes can increase. TGT learning at SMP Muhammadiyah Parepare Class VIII A can optimize student learning outcomes during the learning process, as evidenced by the existence of indicators of understanding, attention, involvement and cooperation. The overall level of student activity in cycle I was 54.37%, and increased in cycle II by 71.87%, so it can be said that from the adequate category to the good category